Functional genetic variants of XRCC4 and ERCC1 predict survival of gastric cancer patients treated with chemotherapy by regulating the gene expression. Issue 12 (11th September 2017) - Cheng, Lei; Qiu, Lixin; Wang, Mengyun; Zhang, Ruoxin; Sun, Menghong; Zhu, Xiaodong; Wang, Yanong; Wei, Qingyi
Abstract : DNA repair protects genomic integrity and may modulate chemotherapy efficacy. Few large‐scale studies have evaluated predictive roles of genetic variants of DNA repair genes in survival of Chinese gastric cancer (GCa) patients treated with chemotherapy. Here, we assessed the roles of 35 single nucleotide polymorphisms (SNPs) in DNA repair genes in survival of 1002 GCa patients, of whom 694 received chemotherapy and 308 did not. Among patients receiving chemotherapy, the ERCC1 rs2298881A allele was associated with a better survival [hazards ratio (HR) = 0.82, 95% confidence interval (CI) = 0.69‐0.98; P  = 0.03], whereas two XRCC4 SNPs were associated with a worse survival (HR = 1.26, 95% CI = 1.03‐1.54 for the rs10040363G allele, P  = 0.02; and HR = 1.30, 95% CI = 1.06‐1.59 for the rs2075685T allele, P  = 0.01). These three SNPs were unique survival predictors for patients treated with chemotherapy ( P  < 0.05 for all) but not for patients without chemotherapy ( P  > 0.05 for all), suggesting that they modulated chemotherapy efficacy. Patients who received chemotherapy and had haplotypes with at least one death‐risk allele in XRCC4 had a poor survival, and the trend for an increase in the number of death‐risk alleles adversely affecting the survival was also observed in an allelic dose‐dependent manner ( P trend  = 0.001). Further functional analysis revealed that the death‐risk alleles up‐regulated the gene expression, leading to a worse survival as suggested by our meta‐analysis pooling both mRNA microarray data from the GEO database and published data ( ERCC1 : HR = 1.31 [1.08‐1.58]; P  = 0.006). These functional genetic variants may independently or jointly affect survival in chemotherapy‐treated GCa patients by modulating the gene expression in the tumors.